Assessment of Ziziphus mauritiana grown on fly ash dumps: Prospects for phytoremediation but concerns with the use of edible fruit. Issue 12 (15th October 2018) - Pandey, Vimal Chandra; Mishra, Tripti
ABSTRACT: A field study was carried out on fly ash (FA) dumps of Panki Thermal Power Station to assess the phytoaccumulation of elements in various plant parts of edible fruit tree Ziziphus mauritiana. Of the twelve analyzed elements, the highest concentration was found for Fe followed by Mn > Se > Zn > Mo > Cu > Cr > Pb > Cd >Ni > As > Co in rhizospheric substrate of Z. mauritiana grown on FA dumps. Metal accumulation, bioconcentration factor, and translocation factor for each metal were calculated in various parts of the edible fruit tree. Significant variations of metal accumulations were observed among various plant parts. Accumulation of toxic elements was higher in roots, and it gradually declined toward the aerial parts of the plant corresponding to its distance from the ground. The concentration of some elements in fruit tree was found to be above prescribed limits in edible parts. Therefore, the present study suggested that additional care should be undertaken, if edible fruit trees are considered for phytoremediation or afforestation programs of FA dumps.